1976
DOI: 10.1080/00039896.1976.10667227
|View full text |Cite
|
Sign up to set email alerts
|

Cell vs. Noncell Airway Temporal Response in Rats Exposed to Sulfur Dioxide

Abstract: A modification of the sulfur dioxide (SO2)-exposed rat model proposed by Reid for the study of chronic bronchitis was employed to evaluate mucus retention and cytologic changes. Rats were exposed to from 600 to 700 ppm of SO2 for 3 hours per day, and groups were examined after 0, 9, 18, and 30 hours of cumulative exposure. Tracheal mucus retention and statistically significant increases (two- to four-fold) in the amount of solid material (cellular and mucus) recovered by bronchia lavage developed as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…SO 2 -induced bronchitis in the rat has been considered a model of chronic human bronchitis because mucus hypersecretion and chronic mucus cell metaplasia are persistent and progressively increased during the course of SO 2 exposure (Farone et al, 1995;Knauss et al, 1976). The concentrations of SO 2 used for developing bronchitis range from 200 to 600 ppm, depending on animal species and strain.…”
Section: Discussionmentioning
confidence: 99%
“…SO 2 -induced bronchitis in the rat has been considered a model of chronic human bronchitis because mucus hypersecretion and chronic mucus cell metaplasia are persistent and progressively increased during the course of SO 2 exposure (Farone et al, 1995;Knauss et al, 1976). The concentrations of SO 2 used for developing bronchitis range from 200 to 600 ppm, depending on animal species and strain.…”
Section: Discussionmentioning
confidence: 99%
“…There are inflammatory cells in the airway lumen as well as the airway tissue of rats with SO 2 ‐induced bronchitis. For example, inflammatory cells are observed in mucus isolated from these rats and increase in number with increasing duration of exposure [44]. We have also observed increased numbers of neutrophils in nasal, airway, and bronchoalveolar lavage fluid of SO 2 ‐exposed rats [37].…”
Section: Animal Models Of Chronic Bronchitismentioning
confidence: 92%
“…[43] reported an elevation in mucous content in bronchoalveolar lavage fluid obtained from SO 2 ‐exposed rats, while Knauss et al . [44] reported that the amount of mucus recovered increased with increasing duration of exposure. Taken together, these data indicate that chronic exposure of rats to SO 2 induces airway mucous hypersecretion.…”
Section: Animal Models Of Chronic Bronchitismentioning
confidence: 99%